Investigation of albumin adsorption on DK-I-56-1 nanocrystals by dynamic light scattering - Mitrović, Jelena; Knutson, Daniel; Nikolić, Ines; Cook, James; Savić, Miroslav; Savić, Snežana (Archives of Pharmacy, 2022)
After parenteral administration, nanoparticles interact with different proteins, forming a shell called corona, which further influence nanoparticles’ biodistribution. Protein adsorption is affected by particle size and shape, but also by molecular interactions of chemical groups from the particle surface and amino-acid residues of the proteins. In human plasma, albumin is the most abundant protein so it is frequently used for the investigation of protein-nanoparticle interactions. In this study we investigated the attachment of bovine serum albumin (BSA) to recently developed nanocrystals of DK-I-56-1 (7‑methoxy‑2-(4‑methoxy‑d3-phenyl)-2,5-dihydro-3H-pyrazolo[4,3-c]quinolin-3-one), stabilized by polysorbate 80 (NS2) or the combination of polysorbate 80 and poloxamer 407 (NS4). Nanocrystal dispersion was incubated in medium containing 0.1% or 1% BSA in phosphate buffer saline (pH 7,4) at 37 °C for 1 h. Particle size analysis was conducted by dynamic light scattering in 10 min interval, at 37 °C on Zetasizer ZS90 (Malvern Instruments Ltd., Worcestershire, UK). It was shown that albumin adsorption was influenced by the nanocrystal formulation and albumin concentration, but not incubation time. In a medium with 0.1% BSA, no particle size difference was noticed in either formulation. However, in case of NS2, after the addition of 1% albumin, particle size and particle size distribution increased, which indicated albumin binding. On the other hand, in formulation NS4, with higher albumin concentration two peaks were visible, one from the free albumin, and one from nanocrystal particles. Therefore, it could be concluded that the affinity of albumin was influenced mainly by the interaction with the nanocrystal stabilizers.